Film out of theatre: D.W. Griffith, Birth of a Nation and the melodrama The Clansman. - Martin, Jeffrey B. (Literature Film Quarterly, 1990)
Compares D.W. Griffith's film adaptation `The Birth of a Nation' and Thomas Dixon's novel `The Clansman' from which the film was adapted. Focus on the degree to which Griffith used or discarded material drawn from the book; Similarity in both subject matter and dramatic structure; Centrality of Dixon's play to Griffith's adaptation.